Diabetes increases mechanical sensitivity and causes morphological abnormalities in the sural nerve that are prevented by treadmill training. Issue 1 (5th October 2012) - Severo Do Nascimento, Patrícia; Lovatel, Gisele Agustini; Ilha, Jocemar; Schaan, Beatriz D'agord; Achaval, Matilde
Abstract Introduction: In this investigation we evaluated the effects of treadmill training on mechanical sensitivity and sural nerve morphology in diabetic rats. Methods: Rats were divided into 3 groups: control (C); diabetic (D); and trained diabetic (TD). Training was performed for 8 weeks. Mechanical sensitivity was evaluated using von Frey filaments. Sural nerve analysis included fiber area, diameter, density of myelinated fibers, area occupied by connective tissue, myelin sheath thickness, and g‐ratio. Results: Animals in the D group had a reduced mechanical sensitivity threshold. Morphometric study showed that the D group had a smaller myelinated fiber area and diameter, higher density of fibers and area occupied by connective tissue, thinner myelin sheath, and higher g‐ratio. The D group had a higher percentage of small myelinated fibers and a lower percentage of large‐diameter myelinated fibers than the C and TD groups. Conclusion: Training prevents functional and morphological abnormalities in the sural nerve caused by diabetes. Muscle Nerve, 2013